Pertanggungjawaban Negara Atas Kejahatan Kemanusiaan Terhadap Etnis Rohingya di Myanmar Antara Kurun Waktu Tahun 2017-2018 - Akbar Kusuma Wardana; Anugrah Adiastuti (Faculty of Law Universitas Sebelas Maret, 2019)
This article describes and reviews the State’s responsibility for crimes against Rohingya in Myanmar during 2017-2018. The research methodology used is a normative research method which has the same resolution as doctrinal research with the nature of prescriptive research based on primary and secondary legal materials. Based on the results of the study, the author obtained the results of Myanmar research discussing several international legal regulations. In this case Myanmar can be held accountable as a punishment for the perpetrators involved in the event. If Myanmar is unable and unable to punish the perpetrators, the International Criminal Court (ICC) can carry out punishments that are in accordance with its jurisdiction. Rome Statute. Article 5 paragraph (1). Anyone who makes coverage will be determined by the individual in accordance with the Rome Statute Article 25 paragraph (2) and will be tried without any difference regarding the Terms or Position in accordance with Article 27.